Autistic traits in the general population do not correlate with a preference for associative information. (January 2017) - Goris, Judith; Deschrijver, Eliane; Trapp, Sabrina; Brass, Marcel; Braem, Senne
Highlights: We replicate the finding that humans have a preference for associative information. We hypothesized that autism traits are related to an enhancement of such preference. The present results show no relation between this preference and autism traits. Abstract: Background: Associations and regularities in our environment can foster expectations and thereby help create a perceptually predictable world (e.g., a knife next to a plate predicts with high certainty a fork on the other side). Based on several observations, it has been suggested that individuals with autism spectrum disorder (ASD) have an above average tendency to prefer well-organized information or structured environments. Surprisingly, however, this tendency has not yet been tested under controlled experimental conditions. Method: A recent study suggested that neurotypical adults prefer associative information, regardless of their semantic content. Therefore, in this study, we examined the relation of this preference bias to the scores of 123 neurotypical adults on questionnaires that measure autistic traits, known to co-vary with typical autism spectrum characteristics. Participants were presented with different configurations of meaningless abstract shapes. Some shapes were always presented in the exact same fixed configuration, and other shapes were always presented in different random configurations. In an unannounced subsequent evaluation task, participants were required to indicate which shapes they preferred. Results: We replicate the observation that people exhibit a general preference for shapes that were presented in fixed configurations. However, there were no correlations between autistic traits and this general preference. Conclusions: Our findings suggest the preference for associative information in ASD might be less general than first thought, or restricted to more complex (social) situations or other levels of information processing. We outline specific guidelines for future systematic investigations into the hypothesized increased preference for associative information in ASD.